Les dimensions de l'espace sonore : concevoir l'expérience du public dans une installation immersive - Simon, Agathe (HAL CCSD, 2023)
International audience Following residencies in the polar regions, Arctic Music, a 5.1 immersive sound installation, is created. During the post-production, the question arises of how best to conceive the experience of the public within such an apparatus. Yet spatialization enables three dimensions of sound space to be deployed: aesthetic, kinaesthetic, and political. It thus offers a singular experience, potentially opening up the audience to an ecological awareness. Suite à des résidences dans les régions polaires, Arctic Music, une installation sonore immersive en 5.1 est créée. Lors de la post-production, la question se pose de concevoir au mieux l'expérience du public au sein d'un tel dispositif. Or la spatialisation permet de déployer trois dimensions de l'espace sonore : esthétique, kinesthésique et politique. Elle propose ainsi une expérience singulière, ouvrant potentiellement le public à une prise de conscience écologique.